The role of sustainable marketing in achieving marketing efficiency Field study in the General Company for Metallurgical Industries / Barada / - Nassour, Rizane (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This study aims to determine the role of elements of sustainable marketing mix in achieving marketing efficiency in General Company for Metallurgical Industries (Barada(. This was done using the descriptive approach. A questionnaire consisting of a set of questions related to the studied research variables and distributed to a sample of workers in General Company for Metallurgical Industries (BARDA). The data were analyzed using the SPSS program. And the study reached a number of results. 1- There is a statistically significant relationship between the sustainable product and achieving marketing efficiency in General Company for Metallurgical Industries (Barada). 2- There is a statistically significant relation between sustainable pricing and marketing efficiency in the General Company for Metallurgical Industries (Barada) 3 - There is a statistically significant relationship between the sustainable distribution and marketing efficiency in the General Company for Metallurgical Industries (Barada). 4- There is a statistically significant relationship between the sustainable promotion and marketing efficiency in the General Company for Metallurgical Industries (Barada). The researcher also presented a set of proposals and recommendations that are expected to help the company's employees develop the working means in the company to reach a competitive position by establishing its marketing efficiency in the Syrian market. تهدف هذه الدراسة إلى تحديد دور عناصر المزيج التسويقي المستدام في تحقيق الكفاءة التسويقية في الشركة العربية للصناعات المعدنية /بردى/ وتم ذلك باستخدام على المنهج الوصفي الإحصائي حيث تم تصميم استبيان مؤلف من مجموعة من الأسئلة المتعلقة بمتغيرات الدراسة المدروسة, والتي تم توجيهها لعينة من العاملين في الشركة العربية للصناعات المعدنية /بردى/ , ومن ثم تم تحليل البيانات باستخدام برنامج حزمة البرامج الإحصائية الجاهزة للعلوم الاجتماعية S.P.S.S، ، توصلت الدراسة إلى مجموعة من النتائج كان من أهمها: 1- توجد علاقة ذات دلالة احصائية بين المنتج المستدام وتحقيق الكفاءة التسويقية في الشركة العربية للصناعات المعدنية /بردى/. 2- توجد علاقة ذات دلالة احصائية بين التسعير المستدام وتحقيق الكفاءة التسويقية في الشركة العربية للصناعات المعدنية /بردى/. 3- توجد علاقة ذات دلالة احصائية بين التوزيع المستدام وتحقيق الكفاءة التسويقية في الشركة العربية للصناعات المعدنية /بردى/. 4- توجد علاقة ذات دلالة احصائية بين الترويج المستدام وتحقيق الكفاءة التسويقية في الشركة العربية للصناعات المعدنية /بردى/. كما قدّم الباحث من خلال هذه الدراسة مجموعة من المقترحات والتوصيات التي من المتوقع أن تساعد العاملين في الشركة في تطوير سبل العمل ضمن الشركة للوصول بها إلى مركز تنافسي عال من خلال تثبيت كفاءتها التسويقة في السوق السورية.